An investigation into flow and heat transfer of an ultrasonic micro-blower device for electronics cooling applications. (5th August 2016) - Ghaffari, Omidreza; Solovitz, Stephen A.; Ikhlaq, Muhammad; Arik, Mehmet
Highlights: We study the mechanical, thermal, and fluid response of an ultrasonic micro-blower. Optimal cooling occurs for jet-to-surface spacings of 15–30 jet diameters. The flow differs from a steady jet over the first 10 diameters past the exit. The best COP occurs at a frequency above the resonant condition. Abstract: As compact electronics increase in functionality, new electronics cooling approaches must be more effective, and they must be lower in form factor. In this paper, we investigated the cooling performance of a miniature ultrasonic micro-blower impinging upon a vertical heater. We studied the temperature response at different operating conditions, determining the optimal thermal conditions. We further examined the local flow field using the particle image velocimetry (PIV) technique at the same operating conditions, providing explanations for the heat transfer response in terms of the fluid dynamics. Heat transfer measurements show that the maximum cooling performance occurs at a jet-to-surface spacing ratio of 15 < H / D < 30, and the performance slowly decays when the jet is located further away. The preferred operating frequency of the piezoelectric cooling device occurs at an ultrasonic frequency of over 20 kHz, meaning that this device can function outside the human hearing range. The PIV results demonstrate that the jet profile in the near field deviates significantly from a traditional turbulent free jet. In the far field, it nearly matches the self-similar, fully-developed jet profile. The jet cooling performance is sensitive to the frequency, with the thermal performance dropping by a factor of six when varying by less than 1 kHz from the peak. At the optimal heat transfer condition, the coefficient of performance is measured at approximately three, which is lower than that of some synthetic jets.